Combination of 16S rRNA and procalcitonin in diagnosis of neonatal clinically suspected sepsis. Issue 3 (October 2020) - Yu, Renqiang; Zhou, Qin; Jiang, Shanyu; Mei, Yingzi; Wang, Min
Objective: To investigate the application of 16S rRNA in diagnosing patients with neonatal sepsis. Methods: We studied 60 consecutive neonatal patients with clinically suspected sepsis and 20 non-infective cases as controls. All patients were diagnosed with sepsis by clinical and experimental criteria. Clinical characteristics were recorded and 16S rRNA sequencing was conducted for all patients. The sensitivity, specificity, and accuracy of the detection methods were analyzed. Results: The detection limit of 16S rRNA sequencing was 1 × 10 2 CFU/mL. For suspected sepsis, the positive rate of 16S rRNA detection was 93.3%, which was similar to that of procalcitonin detection (85%), and was significantly higher than that of bacterial culture (51.7%). The specificity of procalcitonin detection (74.1%) was significantly lower than that of 16S rRNA detection (100%). Moreover, the combination of 16S rRNA and procalcitonin detection showed a sensitivity of 100%, specificity of 74.1%, and accuracy of 92.0%. For proven sepsis, the sensitivity and specificity of 16S rRNA detection were both 100.0%, and those for procalcitonin were 87.1% and 87.0%, respectively. Conclusion: Detection of 16S rRNA has high sensitivity and specificity in diagnosing sepsis. The combination of 16S rRNA and procalcitonin has even better sensitivity with acceptable specificity.